2021
DOI: 10.1049/ise2.12018
|View full text |Cite
|
Sign up to set email alerts
|

Detecting human attacks on text‐based CAPTCHAs using the keystroke dynamic approach

Abstract: A Completely Automated Public Turing Test to Tell Computers and Humans Apart (CAPTCHA) is a simple test that is used on websites to differentiate between human users and automated attacks that indulge in spamming and other fraudulent activities. A text-based CAPTCHA is the most popular security technique used by many websites on the Internet, such as Microsoft, Google and eBay, to secure their sites from automated attacks. By design, however, a CAPTCHA is unable to differentiate between a legitimate human user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…-CAPTCHA-solving services that employ human users (e.g., [45]) are still an attack to adversarial CAPTCHAs, since CAPTCHAs are designed to be recognized by humans. Despite the fact that a recent study in [2] proposed a CAPTCHA system against human-based attacks by exploiting the keystroke dynamics authentication system, this should be investigated in the context of adversarial CAPTCHA schemes.…”
Section: Observation Based On the Analysed Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…-CAPTCHA-solving services that employ human users (e.g., [45]) are still an attack to adversarial CAPTCHAs, since CAPTCHAs are designed to be recognized by humans. Despite the fact that a recent study in [2] proposed a CAPTCHA system against human-based attacks by exploiting the keystroke dynamics authentication system, this should be investigated in the context of adversarial CAPTCHA schemes.…”
Section: Observation Based On the Analysed Studiesmentioning
confidence: 99%
“…CAPTCHAs may come in different forms, including video-based, text-based and imagebased CAPTCHAs. For example, the text-based CAPTCHA prompts users to recognize a text, a task that state-of-the-art text recognition programs cannot complete successfully; due to its various advantages, this form of CAPTCHA is the most commonly deployed type used by websites to date [2].…”
Section: Introductionmentioning
confidence: 99%
“…[39], in which the authors investigated a number of studies on anomaly detection using authentication via keystroke dynamics, wherein they observed that a text length of 10 characters was typical in keystroke dynamics authentication. This text length has proved to be effective when applied with a text-based CAPTCHA to detect attacks from humans [40]. However, the proposed system asks the user to solve a CAPTCHA seven times.…”
Section: Typing Textmentioning
confidence: 99%
“…The number of participants and their division into groups was very similar to the method adopted in most of the previous studies, for example, study of Ref. [40]. Thus, the results of these studies were all considered to be equally credible.…”
Section: Main Experimentsmentioning
confidence: 99%
See 1 more Smart Citation